Skin Changes in Newly Diagnosed Cases of Hypothyroidism - Furquana Niaz, Nadia Shams, Lubna Meraj, Sadaf Ahmed, Najia Ahmed, Irfan Sheikh, Furquana Niaz, Nadia Shams, Lubna Meraj, Sadaf Ahmed, Najia Ahmed, Irfan Sheikh (Journal of Rawalpindi Medical College, 2022)
Introduction: Thyroid disorders are frequent in our population that leads to variety of cutaneous manifestations. Aim of our study was to determine the frequencies of skin changes of hypothyroidism and their association with gender. Methodology: This observational study was conducted at RIHS Islamabad (Ist Jun to 31st Dec 2019) after ethical approval. 105 patients (>18years age) of both genders. Confirmed to have hypothyroidism on the basis of thyroid function tests were included. Secondary hypothyroidism, sick thyroid disease, pregnant women, receiving thyroxin therapy, carcinoma of thyroid, critically ill cases, post-thyroidectomy and iatrogenic thyroid cases were excluded. After informed consent, demographic details were documented. Patients were clinically evaluated and examined in detail including dermatological examination for cutaneous manifestations. Various skin findings are studies with respect to gender. Data was analysed by SPSS version 21 with Chi-square test as a test of significance, significant p<0.05. Results: Among 105 cases of hypothyroidism (62% females and 38% males, mean age was 38.04+12.61 years. Mean TSH level was found to be 32.08 + 33.96 (mean TSH was 35.31+37.31 in females Vs. 26.96 + 27.19 in males; p=0.001). Common skin findings were dry skin in 69.5%, diffuse hair loss in 58%, coarse skin in 57%, pruritis in 51.4%, madarosis 37%, seborrheic dermatitis 34%, coarse scalp hairs 27% and slow nail growth in 23%. The brittle nails, alopecia areata, chronic urticaria, acanthosis nigricans, ivory yellow skin, purpura ecchymosis, ichthyosis, herpes simplex and certain other findings were found in <20% cases. Obesity was observed in 53(50.5%) cases, Type 2 diabetes in 20(19%), hypertension in 23(21.9%), dyslipidaemia in 12(11.4%) and anaemia in 9(8.6%). Obesity, diabetes, dyslipidaemia had no association with gender (p>0.05). However, hypertension and anaemia were significantly frequent amongst females (p<0.05). The dry, coarse skin, diffuse hair loss and seborrheic dermatitis were associated with female gender (p>0.05). Slow nail growth, brittle nails, acne vulgaris, acrochordons, vitiligo, xanthelasma were more common in males however the difference wasn’t statistically significant. Conclusion: Skin acts as an important diagnostic window to diseases affecting internal organs including thyroid disorders. Authors recommend screening for thyroid functions, diabetes, hypertension, dyslipidaemia, obesity and anaemia in patients presenting with suggestive dermatological manifestations irrespective of age and gender. KEYWORDS: Hypothyroidism. Thyroid Diseases. Skin Changes. Thyroid Stimulating Hormone. Thyroid Gland.